BIM coordinators: a review. Issue 8 (17th September 2018) - Jacobsson, Mattias; Merschbrock, Christoph
Abstract : Purpose: The purpose of this paper is to explore the role, practices and responsibilities of building information modeling (BIM) coordinators (BCs). Design/methodology/approach: The aim is achieved through a review of existing publications ( n =183) in which the term "BIM coordinators" has been described and discussed ( n =78), complemented by interviews with four Norwegian BIM experts. Findings: The findings from the review indicate that the core responsibilities of BCs involve clash detection, managing information flows and communication flows, monitoring and coordinating design changes, supporting new working procedures and technical development and acting as a boundary spanner. The complementary interview study extends these findings with two additional practices and a reflection on the experienced challenges, obstacles and potential future development of the role. In essence, the authors propose that the role of BCs can be defined as being responsible for external/internal alignment and coordination of actor needs, and engaged in product-, process- and system-oriented practices of BIM. Research limitations/implications: Given that this study is primarily an integrative literature review of BCs, it has the limitations common with such an approach. Therefore, future studies should preferably extend presented findings through either a survey, further in-depth interviews with BCs or reviews of closely related BIM specialist roles such as BIM managers or BIM technicians. Practical implications: With BCs seemingly being central to information management and knowledge domain integration within the architecture, engineering and construction industry, an understanding of their importance and role should be of interest to anyone seeking to tap into the potential of BIM. This paper outlines specific implications for construction manager, educators and BCs. Originality/value: The value of this study lies primarily in the fact that it is the first thorough investigation of the role, practices and responsibilities of BCs.